The continuous measurement of the springboard reaction force in gymnastic vaulting - Sano, S.; Ikegami, Y.; Nunome, H.; Apriantono, T.; Sakurai, S. (Journal of Sports Sciences, 2007)
A new method was established for the continuous measurement of force applied from a springboard to a gymnast in vaulting (board reaction force). Male gymnasts performed a handspring vault using a springboard mounted on force platforms. A high-speed video camera sampled the springboard motion at 500 Hz. The springboard was initially partitioned into 29 segments. The force due to the accelerative motion of the springboard was determined by summing the forces of the individual segments. The board reaction force acting on the gymnast was calculated by subtracting the force due to the accelerative motion of the springboard and weight from the force recorded by the force platform. The new method succeeded in illustrating transient changes of the board reaction force. The horizontal and vertical components of the peak values of the board reaction force were three and two times greater respectively than the average values. A series of tests was conducted to determine whether the number of segments of the springboard model could be reduced without affecting accuracy. A model consisting of only four segments produced almost the same accuracy as the 29-segment model. The simplified model is recommended as a more efficient method to measure board reaction force.